Clinical anxiety promotes excessive response inhibition. Issue 3 (25th October 2016) - Grillon, C.; Robinson, O. J.; O'Connell, K.; Davis, A.; Alvarez, G.; Pine, D. S.; Ernst, M.
Abstract : Background: Laboratory tasks to delineate anxiety disorder features are used to refine classification and inform our understanding of etiological mechanisms. The present study examines laboratory measures of response inhibition, specifically the inhibition of a pre-potent motor response, in clinical anxiety. Data on associations between anxiety and response inhibition remain inconsistent, perhaps because of dissociable effects of clinical anxiety and experimentally manipulated state anxiety. Few studies directly assess the independent and interacting effects of these two anxiety types (state v. disorder) on response inhibition. The current study accomplished this goal, by manipulating state anxiety in healthy and clinically anxious individuals while they complete a response inhibition task. Method: The study employs the threat-of-shock paradigm, one of the best-established manipulations for robustly increasing state anxiety. Participants included 82 adults (41 healthy; 41 patients with an anxiety disorder). A go/nogo task with highly frequent go trials was administered during alternating periods of safety and shock threat. Signal detection theory was used to quantify response bias and signal-detection sensitivity. Results: There were independent effects of anxiety and clinical anxiety on response inhibition. In both groups, heightened anxiety facilitated response inhibition, leading to reduced nogo commission errors. Compared with the healthy group, clinical anxiety was associated with excessive response inhibition and increased go omission errors in both the safe and threat conditions. Conclusions: Response inhibition and its impact on go omission errors appear to be a promising behavioral marker of clinical anxiety. These results have implications for a dimensional view of clinical anxiety.